2022
DOI: 10.3389/fmicb.2022.1079136
|View full text |Cite
|
Sign up to set email alerts
|

The role of microbial ecology in improving the performance of anaerobic digestion of sewage sludge

Abstract: The use of next-generation diagnostic tools to optimise the anaerobic digestion of municipal sewage sludge has the potential to increase renewable natural gas recovery, improve the reuse of biosolid fertilisers and help operators expand circular economies globally. This review aims to provide perspectives on the role of microbial ecology in improving digester performance in wastewater treatment plants, highlighting that a systems biology approach is fundamental for monitoring mesophilic anaerobic sewage sludge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 168 publications
1
4
0
Order By: Relevance
“…In the present study, we demonstrated the capability of Methanosaeta to exist in both mesophilic and thermophilic conditions and its resiliency in surviving temperature changes while becoming the most predominant biogas producer via an acetoclastic pathway. This finding strengthens the earlier discovery that the abundance of acetoclastic methanogen (such as Methanosaeta) can provide reliable CH 4 production and stability indicators [48]. Instead of temperature, the metabolic shift of abundance from Methanosaeta to Methanosarcina may occur if Methanosaeta cannot produce methane due to specific environmental changes such as acetate availability, decreasing pH, increasing organic loading rates, high levels of salts, and ammonia nitrogen [6,49,50].…”
Section: Discussionsupporting
confidence: 85%
“…In the present study, we demonstrated the capability of Methanosaeta to exist in both mesophilic and thermophilic conditions and its resiliency in surviving temperature changes while becoming the most predominant biogas producer via an acetoclastic pathway. This finding strengthens the earlier discovery that the abundance of acetoclastic methanogen (such as Methanosaeta) can provide reliable CH 4 production and stability indicators [48]. Instead of temperature, the metabolic shift of abundance from Methanosaeta to Methanosarcina may occur if Methanosaeta cannot produce methane due to specific environmental changes such as acetate availability, decreasing pH, increasing organic loading rates, high levels of salts, and ammonia nitrogen [6,49,50].…”
Section: Discussionsupporting
confidence: 85%
“…The other factor affecting the extent of foaming is the presence of certain microbes and the biosurfactants and hydrophobic substances they produce [9]. Gordonia, a genus implicated in wastewater digester foaming [47,123], was detected from the beginning of the acclimatisation period until foaming event B. Microthrix was also identified but steadily decreased in relative abundance throughout the digestion period [40].…”
Section: Source-separated Wastewater Potentialmentioning
confidence: 99%
“…The extent and stability of digestion, and therefore the composition and volume of biogas, are affected by a range of parameters, including design decisions such as reactor configuration [6], temperature [7,8], and retention time [8], together with chemical properties of the feedstock and reaction medium, such as pH and elemental balance, and the microbial community [9].…”
Section: Introductionmentioning
confidence: 99%
“…The generalist groups can perform similar ecological functions in a reactor and this redundancy ensures that even when the environmental conditions change, the ecosystem will stay functional, because its functional niches are occupied (Krohn et al 2022;Zhu et al 2020).…”
Section: Notementioning
confidence: 99%